2009
DOI: 10.1063/1.3056414
|View full text |Cite
|
Sign up to set email alerts
|

Vortex formation in a cavity with oscillating walls

Abstract: The vortex formation in a two-dimensional Cartesian cavity, which their vertical walls move simultaneously with an oscillatory velocity and the horizontal walls are fixed pistons, is studied numerically.The governing equations were solved with a finite element method combined with an operator splitting scheme. We analyzed the behavior of vortical structures occurring inside a cavity with an aspect ratio of height to width of 1.5 for three different displacement amplitudes of the vertical oscillatory walls (amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…The bottom wall shear layer is a result of the vortex (with positive vorticity) shed from the cylinder bottom, a region with negative vorticity occurs between the vortex and the wall. This result is valid for a vortex in the vicinity of a wall as first predicted by Peace and Riley, 45 observed experimentally by Walker et al 46 and Allen and Chong, 47 and shown by Ovando et al 48 and Zhu et al 49 using numerical simulations. This flow is denoted as wake pattern A.…”
Section: Wake Patternssupporting
confidence: 84%
“…The bottom wall shear layer is a result of the vortex (with positive vorticity) shed from the cylinder bottom, a region with negative vorticity occurs between the vortex and the wall. This result is valid for a vortex in the vicinity of a wall as first predicted by Peace and Riley, 45 observed experimentally by Walker et al 46 and Allen and Chong, 47 and shown by Ovando et al 48 and Zhu et al 49 using numerical simulations. This flow is denoted as wake pattern A.…”
Section: Wake Patternssupporting
confidence: 84%